Mathematising of Coding Education Command: Focusing on Algebra Education - Jinhwan Jeong; hanhyuk Cho (Korea Society of Educational Studies in Mathematics, 2020)
Mathematics is at the root of coding and AI convergence education, emphasized in recent school education. This paper proposes an education content and education method that can combine elementary and secondary coding education that is being introduced recently with school mathematics in a developmental way. Specifically, in this paper, through the mathematising of the code in coding education, the contents of education to develop from arithmetical coding to algebraic coding are designed, as well as the minimum coding mapping strategy that induces development into algebraic coding. Additionally, this study addresses and analyzes the process in which learners develop their algebraic abilities with educational content and guidance strategies that converge coding education in elementary and secondary schools into math education, especially algebra education. This convergence education is achieved through a Papert's constructionism learning theory-based artifact design, and the minimum code strategy is designed to enable learners to form a knowledge structure of algebra and gain experience in exercising computational thinking.